Effect of methionine hydroxy analog feed supplements: Significant alteration and enrichment of rumen microbiota and metabolome in Hu sheep - Li, Shujie; Zeng, Hanfang; Wang, Changjian; Han, Zhaoyu (Frontiers in Veterinary Science, 2022)
Methionine hydroxy analogs (MHA) are widely used as the main sources of methionine in ruminant feed production. However, studies that have compared various MHA and their effects on rumen microorganisms and metabolites are few. The objective of this study was to investigate the effect of using MHA supplements such as MHA as a salt of calcium (MHA-Ca) and 2-hydroxy-4-(methylthio)-butanoic acid isopropyl ester (HMBi) as sources of methionine on the rumen microbiota and metabolome in Hu sheep. Seventy-two healthy Hu sheep were randomly assigned to three dietary treatment groups: control, MHA-Ca, and HMBi groups. The results showed that the concentrations of total volatile fatty acids, acetate, and propionate were higher in the HMBi group than in the control group. The HMBi and MHA-Ca groups had higher alpha diversity values than those in control group. We compared the rumen microbiota by Using 16S rRNA gene sequencing. At the phylum level, the HMBi group had a higher relative abundance of Firmicutes and a lower relative abundance of Synergistetes than did the control group. At the genus level, the control group had a higher relative abundance of Treponema_2 than did the HBMi group and a higher relative abundance of Prevotellaceae_UCG_004 than did the MHA-Ca group. Metabolomic analyses revealed that fatty acids, amino acids, lipids, organic acids, sugars, amines, and nucleosides were significantly altered in both MHA-Ca and HMBi groups. Metabolites with significant differences were enriched in amino acid and carbohydrate metabolisms, such as phenylalanine metabolism, biosynthesis of amino acids, tryptophan metabolism, galactose metabolism, and tyrosine metabolism. Above all, the findings presented in this study indicate that MHA alter the rumen microbiota and metabolites and that different forms of MHA have different impacts. Our findings contribute to a deeper understanding of the effects of MHA.